Why does the poor worker keep living poorly in Aceh, Indonesia? - Chenny Saftarita, T. Zulham,; Bahran Basyiran, Teuku; Ilhamudin, Tasdik; Saputra, Jumadil (Opción, 2019)
This study aims to analyse the determinants of income for poor workers concerning social demographic variables. Social demographic variables are the most likely determinants in affecting the income level of working poor in which variable age, marital status, employment, and the number of family members have strongly significant impacts. Of the goals of study is to estimation results which are highly relevant to the government's task to accelerate economic growth and to effectively implement family planning programs in encouraging the delay of marriage age and population control.